The Digital Transformation Paradox: A Systematic Literature Review of Online Single Submission (OSS) Implementation in Indonesia - Fathimah Qotrunnada Al Jannah; Sidik Pramono (Department of Government Studies, Faculty of Social and Political Sciences, Universitas Syiah Kuala, 2025)
The Online Single Submission system was launched as a major reform to streamline business licensing in Indonesia, particularly for Micro, Small, and Medium Enterprises. However, this promise of efficiency clashes with the challenging realities of its implementation. Through a Systematic Literature Review, this study uncovers the root causes of these issues by mapping the key factors determining the success and failure of the OSS. The analysis covers 21 relevant Scopus-indexed articles, utilizing the PRISMA framework to ensure a systematic and transparent review process. The synthesis of findings reveals a central paradox: while the OSS is conceptually a breakthrough, its implementation is paralyzed by governance issues. Three main obstacles consistently emerge: poor integration of data and authority among government agencies, bureaucratic resistance driven by sectoral egos, and low digital literacy among MSMEs, the system's primary target users. This study concludes that the source of the OSS's failure lies not in its technological sophistication, but rather in the fragile interplay between policy, institutions, and user capacity. Therefore, the success of future reforms depends on a genuine commitment to improving governance, not merely on refining the digital platform.